Tinjauan Apologetis-Teologis Terhadap Skeptisisme Ke-Tuhan-an Yesus Menurut Kitab Injil - Yakobus Adi Saingo (JURNAL LUXNOS, 2022)
Abstract: This study aims to conduct an apologetic-theological review of the skepticism of the Lordship of Jesus according to the Gospels. This study uses a literature study method and a biblical analysis approach (specifically the Gospels) so that it can describe a general picture of the problems experienced in Christianity related to the divinity of Jesus and apologetic actions (defense of the faith) against those who attack and doubt the divinity of Jesus. The author begins by explaining the theoretical concepts related to the discussion topics so that the author and the reader have the same perception of the concept and the basis of the discussion. Then systematically describe the heresies in Christology, such as Arianism, Docetism, Gnosticism, Monarchianism, Ebionitism, Liberalism, and Jehovah's Witnesses with the factors of Jesus' Divinity Skepticism consisting of elements in Jesus' humanity and divinity. Thus, the researchers also provide solutions regarding apologetic-theological efforts against the skepticism of the divinity of Jesus according to the Gospels, which structurally will explain biblical implicit and explicit evidence, biblical acknowledgment of others/other parties, the biblical confession of behavior biblically, and Christology from the Biblical-Theological Review. All these reviews were conducted to prove that Jesus is a true man and true God. Abstrak: Tujuan penelitian ini adalah melakukan tinjauan apologetis-teologis terhadap skeptisisme ke-Tuhan-an Yesus menurut kitab Injil. Penelitian ini menggunakan metode studi literatur serta pendekatan analisis biblika (khusus kitab Injil), sehingga dapat mendeskripsikan gambaran umum terkait permasalahan yang dialami dalam kekristenan terkait keilahian Yesus serta tindakan apologetik (pembelaan iman) terhadap pihak-pihak yang menyerang dan meragukan keilahian Yesus. Penulis mengawalinya dengan menjelaskan konsep teoritis terkait pokok-pokok pembahasan sehingga antara penulis dan pembaca memiliki persepsi yang sama tentang konsep dan dasar pembahasan. Kemudian secara sistematis mendeskripsikan mengenai bidat dalam Kristologi seperti: Arianisme, Doketisme, Gnostisisme, Monarkianisme, Ebionitisme, Liberalisme maupun Saksi Yehova dengan faktor-faktor Skeptisisme Ke-Tuhan-an Yesus yang terdiri dari faktor kemanusiaan dan faktor keilahian Yesus. Serta, peneliti juga memberikan solusi mengenai upaya apologetis-teologis terhadap skeptisisme ke-Tuhan-an Yesus menurut kitab Injil dimana secara struktural akan memaparkan mengenai bukti implisit dan eksplisit secara biblika, pengakuan orang lain/pihak lain secara biblika, perilaku Ilahi-Nya secara biblika, serta kristologi dari tinjauan teologis-biblika. Semua tinjauan tersebut dilakukan untuk membuktikan bahwa Yesus adalah manusia sejati dan Allah sejati.